THE CASE OF THE E-BOOK IN “SMALL LANGUAGE” CULTURE: MEDIA TECHNOLOGY AND THE DIGITAL SOCIETY - MACEVIČIŪTĖ, ELENA; NILSSON, KERSTI; WILSON, TOM; BERGSTRÖM, ANNIKA; HÖGLUND, LARS (Knygotyra, 2014)
The article describes a research project conducted in Sweden and its initial base-line results that were produced by investigating statistical data from general statistical sources, representative surveys of the Swedish population, and from public and academic libraries. The project looks into the change introduced into the book sector by e-books. Sweden was chosen as a special case – a country with a high literacy level and high penetration of information technology into everyday life of people. At the same time, the spread of e-books is at the very start and it seems that the diffusion of e-books, their production, distribution and use are affected by the problems characteristic of a typical small publishing markets.The authors present the goals of the project and the theoretical framework. The data were collected in 2012 and demonstrate the relatively low scale of e-book publishing and use. Libraries emerge as the main channel of access to e-books for readers. The usual problems of e-book production and distribution that are visible in other countries are observed in Sweden as well: e-books legally are not books, but services of licensed software and thus excluded from the privileges enjoyed by paper books; readers demand more e-books but are not ready to pay for them the same price as for traditional books and prefer to acquire them through free channels. Publishers seek to maintain the monopoly of e-book distribution and fear piracy. Libraries lose independence of acquisition and collection management. The choice of e-books by readers is determined by access to technology, age and education as well as reading habits.KEYWORDS: digital books, Sweden, publishing industry, reading, book distribution, libraries